Treatment of Snake Bites at a Regional Burn Center: Report of a Case Series - Yu, Gie N; Helmer, Stephen D; Khandelwal, Anjay K (Kansas Journal of Medicine, 2013)
Background. Although uncommon, snakebites can cause significant morbidity and mortality. The objective of this study was to review the characteristics, treatment, and outcome of patients with a suspected or known snakebite who were treated at a regional verified burn center. Methods. A retrospective chart review of all snakebite victims was conducted for the time frame between January 1991 and June 2009. Results. During the study period, 12 patients were identified. One of the twelve patients was excluded because he had been admitted as an outpatient for wound debridement after being initially treated at another facility. Ten of the remaining 11 patients were male (90.9%). Rattlesnakes were responsible for the majority of bites. One of the eleven patients needed a fasciotomy. The majority of patients received antivenin (ACP/fabAV). No anaphylactoid reactions to either antivenin were recorded. There were no deaths. Conclusion. With burn centers evolving into centers for the care of complex wounds, patients with snakebite injuries can be managed safely in a burn center.